Stress Affects Mast Cell Proteases in Murine Skin in a Model of Atopic Dermatitis-like Allergic Inflammation - Rommel, Frank R.; Tumala, Susanne; Urban, Anna-Lena; Siebenhaar, Frank; Kruse, Johannes; Gieler, Uwe; Peters, Eva M. J.; Justus Liebig University Giessen (My University, 2024)
Stress exposure worsens allergic inflammatory diseases substantially. Mast cells (MCs) play a key role in peripheral immune responses to neuroendocrine stress mediators such as nerve growth factor (NGF) and substance P (SP). Mast cell proteases (MCPs) and cholinergic factors (Chrna7, SLURP1) were recently described to modulate MC stress response. We studied MCPs and Chrna7/SLURP1 and their interplay in a mouse model for noise induced stress (NiS) and atopic dermatitis-like allergic inflammation (AlD) and in cultured MC lacking Chrna7. We found that the cholinergic stress axis interacts with neuroendocrine stress mediators and stress-mediator cleaving enzymes in AlD. SP-cleaving mMCP4+ MC were upregulated in AlD and further upregulated by stress in NiS+AlD. Anti-NGF neutralizing antibody treatment blocked the stress-induced upregulation in vivo, and mMCP4+ MCs correlated with measures of AlD disease activity. Finally, high mMCP4 production in response to SP depended on Chrna7/SLURP1 in cultured MCs. In conclusion, mMCP4 and its upstream regulation by Chrna7/SLURP1 are interesting novel targets for the treatment of allergic inflammation and its aggravation by stress.
Keywords: ddc:610